The Concept of ‘Play’ from the Point of View of Theories of Museology - Jovaišaitė-Blaževičienė, Indrė (Knygotyra, 2022)
In the first decades of the 21st century, the topic of the ‘playing’ person has become the core of interdisciplinary research on human activity. As museums have been adopting a new approach towards cultural dissemination and educational goals, the discourse of play is also becoming one of the current fields of research in museology. Although the cultural aspects of play and game have been discussed for a long time, the interpretation of the concept of play from the museological point of view is a relatively new field which requires the definition of the synonymously used terms and the respective concepts. The aim of this article is to highlight the concept and function of play in museology based on the analysis of museology theories, to identify the preconditions for the formation of play communication, and to identify the directions of the development of the concept of play in the contemporary museological research. The article is based on an integrated literature review of the analysis of the concept of play while focusing on theoretical texts and monographs of scholars studying the phenomenon of play, as well as on theoretical and empirical research articles analysing the expression of play in all types of museums. This paper also discusses the linguistic use of the terms play and game. In the Lithuanian language, we not only have to deal with the synonymous use of play (žaismas)/game (žaidimas) in the translation of spel, play, spielen, but also with the use of play in the translation of both play and game used in different contexts in the English-language literature. Since game is a structured form of play, and, in the museological research and practice, game is more commonly defined as the digital expression and referred to as gamification, it is suggested that play (as an action and a state of being) should be distinguished from game (as a structured form of action) by using two different terms in the Lithuanian language. The literature reviewed in this article has highlighted that the concept of play in the museum is linked to the development of new theories of museology, and it reveals itself as a creative construct that is shaped and sustained by the institution. Play is defined as the concept for communicating the theme of the museum, manifested through the act of play and the elements of game. This approach to the dissemination of content and the organisation of activities is expressed through the application of play and game methods which allow the audience to engage in a more intensive relationship with the museum’s theme and exhibits. Play becomes a necessary medium for the museum’s metagame which includes and expresses playfulness, play action, playful elements, real and digital games, whereas the audience is engaged by play to satisfy its educational and entertainment needs. To summarise on the interdisciplinary context of the phenomenon of play, in museology, it is most appropriate to associate play with an intellectual or conceptual state that involves exchange, change and playful action. The term game in the museological context is more commonly used to refer to a specific spatial, temporal or rule-based action which, in the museum practice, is more frequently associated with gamification.
Keywords: concept of play; play in museology; new museology; theories of museology